Preparation and quality evaluation of flour and biscuits made from red corn powder using as supplement with different ratios of red corn flour - Nguyen Van Toan; Nguyen Thao Thuc Tran, (International Journal of Scientific Research and Management (IJSRM), 2022)
The consumption of cereal foods such as biscuits has become very popular globally. Also, in recent years, nutritional potential is prioritized in every foodstuff. Different types of maize such as yellow, sweet corn are one of well-known healthy ingredients for developing new biscuit products, except red corn. This has spurred pragmatic research on developing biscuits prepared by blending wheat flour with red corn powder in ratios of 5%, 10%, and 15%. This study was, conducted to investigate functional properties of composite flours. The effects of three levels of red corn powder in the physical dimensions, nutritional constituents, consumers’ acceptability and compared to the quality of 100% wheat biscuits. In essence, partial substitution of wheat flour with red corn powder witnessed an increase in protein and fiber. Besides, a significant increase was noticed in total phenolic content and the antioxidant (p